A contextualização do ensino de ciências na Amazônia - Nascimento, Rebeca Brandão (2022)
The present work is an action research with a qualitative approach with the objective of evaluating the potential of approaching the electric fish associated with didactic strategies as a way of contemplating the Teaching of Natural Sciences in Elementary School Final Years in the themes and contents correlated. The methodology used was action research and 5 stages were organized: The first stage consists of collecting information about the place where the research was carried out and selecting the participants. The second step was the application of a questionnaire to collect the students' previous knowledge about the Amazon, the electric fish and the Sciences of Nature. The third stage was the construction of the educational product: a didactic guide for the dissemination of the importance of activities developing Amazonian themes for the development of meaningful learning. In the fourth step, the didactic sequence was applied. In the fifth stage, data analysis was performed using criteria to verify significant learning through scripts and analysis of the didactic sequence, which made it possible to create tables, charts and graphs. The results found show that the use of a didactic sequence can point out that the intention to teach concepts of Natural Sciences from something so regional brought clear results in the responses of the activities proposed in the scripts, presenting sentences, reports with a great connection to the Amazon. , anchored to previous experiences and knowledge, and may consider that the main objective was achieved, showing that the didactic sequence was of great relevance for the meaningful learning of the contents of Natural Sciences